2015
DOI: 10.1111/jace.13605
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence Properties of Er/Pr‐Doped K0.5Na0.5NbO3 Ferroelectric Ceramics

Abstract: Er/Pr-doped K 0.5 Na 0.5 NbO 3 ceramics have been fabricated and the effects of Pr 3+ on their photoluminescence properties have been investigated systematically. The visible upconversion emissions, near-infrared and mid-infrared downconversion emissions of Er 3+ ions under the excitation of 980 nm have been studied in detail. The effects of Pr 3+ on PL properties and energytransfer processes have also been elucidated. By selecting an appropriate excitation source, simultaneous visible downconversion emissions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…The latter was demonstrated that many ferroelectric materials, such as BaTiO 3 , Bi 4 Ti 3 O 12 , K 0.5 Na 0.5 NbO 3 [9] and Na 0.5 Bi 0.5 TiO 3 , are suitable for using as luminescent hosts. Among these materials, Sodium bismuth titanate (Na 0.5 Bi 0.5 TiO 3 , NBT) is considered to be one of the most promising luminescent ferroelectric host.…”
Section: Introductionmentioning
confidence: 97%
“…The latter was demonstrated that many ferroelectric materials, such as BaTiO 3 , Bi 4 Ti 3 O 12 , K 0.5 Na 0.5 NbO 3 [9] and Na 0.5 Bi 0.5 TiO 3 , are suitable for using as luminescent hosts. Among these materials, Sodium bismuth titanate (Na 0.5 Bi 0.5 TiO 3 , NBT) is considered to be one of the most promising luminescent ferroelectric host.…”
Section: Introductionmentioning
confidence: 97%
“…Among these methods, ion doping (e.g., metal ions, transitional metal ions, or lanthanide ions) is widely used to enhance their piezoelectric properties. In particular, lanthanide (Ln) ion doping not only endows KNN‐based materials with the fascinating optical properties, but also can improve their intrinsic ferro‐/piezoelectric properties . The coexistence of luminescent and ferro‐/piezoelectric properties are encouraging for the researchers, which can further expand the application fields of KNN‐based materials as a kind of multifunctional devices by integrating their luminescent and ferro‐/piezoelectric properties.…”
Section: Introductionmentioning
confidence: 99%
“…The uneven crystal field can mix opposite-parity states into the 4f configuration level and then increase the 4f-4f electric dipole transition probability of Pr 3+  1618. Apparently, the polarization switching and phase transformation have opposite effects on PL emissions, and, on the basis of the results (Fig.…”
Section: Resultsmentioning
confidence: 73%
“…4. Three strong excitation peaks arising from the excitations of Pr 3+ from the 3 H 4 ground level to the 3 P 2 , 3 P 1 and 3 P 0 excited levels are observed at 450, 473 and 487 nm, respectively1839. Accordingly, the photoluminescence (PL) emission spectrum of the ceramic has been measured under an excitation of 450 nm, giving the results shown in Fig.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation